Pengaruh Merger dan Akuisisi Terhadap Financial Performance: Studi Merger Bank Yang Terdaftar di Bursa Efek Indonesia - Laurentia Tirza; Josua Tarigan (Business Accounting Review, 2016)
Mergers and acquisitions made by the company with the hope to bring an advantages. Favorable conditions will occur when merger and acquisition obtain synergies. The development of mergers and acquisitions in the Indonesia banking sector began after the 1998 crisis, when the merger is one of the banking rescue efforts were driven by Bank Indonesia to improve the bank performance. Regarding the assessment of bank performance, Bank Indonesia has issued a regulation to assess the bank financial performance, ie through ratio CAMELS (Capital, Asset Quality, Management, Earnings, Liquidity and Sensitivity to Market Risks). Therefore, this study aims to examine the impact of bank merger in terms of the financial performance of the bank based on CAMELS ratio. This research type is comparative with a view to comparing the financial performance before and after merger. Samples were banking companies listed in Indonesia Stock Exchange and the merger during the period 2000-2010. This study uses analysis techniques paired sample t test. The results showed impact of the merger Bank Danamon only significantly on RORA ratio (increase), the impact of the merger Bank Artha Graha only significantly on IRR ratio (decrease), the impact of the merger Bank CIMB Niaga only significantly on CAR ratio (increase) and LDR ratio (increase), and the impact of the merger Bank Permata only significantly on NPM ratio (increase).